Flexural fatigue and fracture toughness behavior of nanoclay reinforced carbon fiber epoxy composites. (December 2020) - Tareq, Md Sarower Hossain; Zainuddin, Shaik; Hosur, Mahesh V; Jony, Bodiuzzaman; Ahsan, Mohammad Al; Jeelani, Shaik
3-point flexural fatigue and Mode I interlaminar fracture tests were done to study the fatigue life and fracture toughness of nanoclay added carbon fiber epoxy composites. Fatigue life data was analyzed using Weibull distribution function, validated with Kolmogorov-Smirnov goodness-of-fit, and predicted by combined Weibull and Sigmoidal models, respectively. The nanophased samples showed more than 300% improvement in mean and predicted fatigue life. At 0.7 stress level, the nanophased samples passed the 'run-out' fatigue criteria (10 6 cycles), whereas, the neat samples failed much earlier. The interlaminar fracture toughness of nanophased samples was also enhanced significantly by 71% over neat samples. Optical and scanning electron microscopic images of the nanophased fractured samples revealed certain features that improved the respective fatigue and fracture properties of the composites.